THE EFFECT OF MURABAHAH FINANCING AND RECEIVABLE INCOME OF PANIN DUBAI SYARIAH BANK ON ROA IN 2010-2019 - Ismaulina Ismaulina; Juliana Putri; Rauzatul Amanda (Univeristas Islam Bandung, 2021)
Panin Dubai Bank has murabahah financing and receivables which play an important role in the wheels of the Indonesian economy. Bank financing income is measured by the level of profitability using the Return on Assets (ROA) formula. This study aims to determine and analyze partially and simultaneously the effect of Mudharabah Receivables and financing on ROA of Panin Dubai Syariah Bank. Using 40 samples from quarterly financial reports for March 2010 - December 2019. Data analysis, using, Classical Assumption Test, Multiple Linear Regression Test, T Test, F Test, Correlation Coefficient, and Coefficient of Determination using SPSS 16. The results showed that partially Mudharabah has no positive and insignificant effect on ROA, while Musyarahah does negative and significant, partially Murabahah Receivables have no negative and significant effect on ROA, and simultaneously Mudharabah Receivables and financing have a significant positive effect on ROA.